Cardiovascular Risk Factors in the Republic of Karelia, Russia, and in North Karelia, Finland - PUSKA, PEKKA; MATILAINEN, TIINA; JOUSILAHTI, PEKKA; KORHONEN, HEIKKI; VARTIAINEN, ERKKI; POKUSAJEVA, SVETLANA; MOISEJEVA, NINA; UHANOV, MIHAIL; KALLIO, IRENA; ARTEMJEV, ANATOLI (International Journal of Epidemiology, 1993)
Cardiovascular disease risk factors were measured in a population survey in Pitkranta District in the Republic of Karelia and in North Karelia in Finland in spring 1992. According to official statistics the cardiovascular mortality in the Republic of Karelia is somewhat higher, and total mortality and cancer mortality considerably higher than in North Karelia. A random sample of the population, aged 25–64 years, was taken in Pitklranta (n = 1000) and in North Karelia (n = 2000). The participation rates were 84% and 74% respectively. The mean total serum cholesterol among men was 5.2 mmol/l in Pitkranta and 5.8 mmol/l in North Karelia (P < 0.001) and among women 5.3 mmol/l and 5.6 mmol/l (P < 0.001 ), respectively. The mean high density lipoprotein (HDL) cholesterol levels among men were 1.4 mmol/l and 1.3 mmol/l (P < 0.001). and among women 1.4 mmol/l and 1.5 mmol/l (P < 0.001). respectively. There were no significant differences in blood pressure among men, but women in Pitkranta had higher blood pressure than women in North Karelia. The mean body mass index in Pitkaranta was higher among women, 28.0 versus 26.5 (P < 0.001) and lower among men, 25.2 versus 27.0 (P < 0.001) than in North Karelia. Smoking was much more common among men (65% versus 31 %) but less common among women (10% versus 16%) in Pitkranta than in North Karelia. The general level of the risk factors, and especially the higher prevalence of smoking among men could explain the high mortality rates in Pitkranta, and in particular the high cancer mortality